What is the Government Really Pursuing by Introducing Quarantine Measures in the Conditions of COVID-19? The Case of Ukraine - Vitalii Nitsenko (International Society of Philosophy and Cosmology (ISPC), 2021)
New challenges in the COVID-19 pandemic for Ukraine turned out not to draw the authorities (President, the Cabinet of Ministers, and the Verkhovna Rada of Ukraine) with people, enhancing support in difficult economic conditions, support for small and medium-sized businesses, and the introduction of quarantine and enhancing control in all spheres of the people life.